“The World Blurred in the Blood” at the Paris Journalism of I. D. Surguchev of Wartime (1940-1945) - A. B. Zamorkin (Научный диалог)
The article is devoted to the specifics of the themes and ideas in Parisian journalism of I. D. Surguchev in 1940-1945 years. The research is based on his diary and publications in the newspapers of the time forming “Paris Diary (1940-1945)” (2015) prepared for publication by well-known Surguchev’s researcher A. A. Fokin. Attention is paid to Serguchev’s characteristic of the time. It is stated that the author acknowledges the tragedy of what is happening, not giving negative evaluations to the occupants. It is shown that in this period Surguchev’s journalism is concentrated around a constant basic categories of being - “eternity,” “culture,” “life,” “death,” “happiness.” It is argued that Surguchev expresses his boundless faith in the power and possibilities of culture. The publicist, creating a picture of universal impoverishment, chaos and decline of morality in wartime, consistently pursued the idea of disastrous fragmentation of society and lack of patriotism. It is reported that Surguchev assessed the Republic as an inefficient form of government. Special attention is paid to the theme of Russia. It is noted that the German invasion of Russia was interpreted by Surguchev as the beginning of liberation from Bolshevism, as the possibility of the return of Russian emigration home.